Analysis of the Effectiveness of Accounts Receivable Management on the Risk of Uncollectible Accounts at Four Seasons Resort Bali at Jimbaran Bay - P Widyantari; I K Sugiarta; P D Hudiananingsih (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
Credit sales policy is one of the strategies implemented by the Four Seasons Resort Bali at Jimbaran Bay management to win the competition. Credit sales have the risk of delays in cash receipts that have the potential to become uncollectible receivables. This study aims to determine and analyze the performance and effectiveness of accounts receivable. This study uses data in the form of receivable aging schedule, data on the number of credit sales, and application form. The analysis used to analyze the lending requirements is the 5C analysis, analyze the management of receivables is the accounts receivable turnover ratio, the average day billing ratio, the arrears ratio, and the billing ratio. The results of this study indicate that the analysis of the performance of receivables reflects the management of receivables that have not been effective because hotel management only takes into account 2 of the 3 principles of 5C. This can be known through the analysis of accounts receivable turnover ratios and the average days of collection of accounts receivable which show below standard results and this has an impact on the results of the arrears ratio and billing ratio.